Brain-inspired modular echo state network for EEG-based emotion recognition - Yang, Liuyi; Wang, Zhaoze; Wang, Guoyu; Liang, Lixin; Liu, Meng; Wang, Junsong (Frontiers in Neuroscience, 2024)
Previous studies have successfully applied a lightweight recurrent neural network (RNN) called Echo State Network (ESN) for EEG-based emotion recognition. These studies use intrinsic plasticity (IP) and synaptic plasticity (SP) to tune the hidden reservoir layer of ESN, yet they require extra training procedures and are often computationally complex. Recent neuroscientific research reveals that the brain is modular, consisting of internally dense and externally sparse subnetworks. Furthermore, it has been proved that this modular topology facilitates information processing efficiency in both biological and artificial neural networks (ANNs). Motivated by these findings, we propose Modular Echo State Network (M-ESN), where the hidden layer of ESN is directly initialized to a more efficient modular structure. In this paper, we first describe our novel implementation method, which enables us to find the optimal module numbers, local and global connectivity. Then, the M-ESN is benchmarked on the DEAP dataset. Lastly, we explain why network modularity improves model performance. We demonstrate that modular organization leads to a more diverse distribution of node degrees, which increases network heterogeneity and subsequently improves classification accuracy. On the emotion arousal, valence, and stress/calm classification tasks, our M-ESN outperforms regular ESN by 5.44%, 5.90%, and 5.42%, respectively, while this difference when comparing with adaptation rules tuned ESNs are 0.77%, 5.49%, and 0.95%. Notably, our results are obtained using M-ESN with a much smaller reservoir size and simpler training process.